High Thermoelectric Performance in Non‐Toxic Earth‐Abundant Copper Sulfide. (26th March 2014) - He, Ying; Day, Tristan; Zhang, Tiansong; Liu, Huili; Shi, Xun; Chen, Lidong; Snyder, G. Jeffrey
<x xml:space="preserve">Abstract</x> A new type of high performance thermoelectric material Cu2‐xS composed of non‐toxic and earth‐abundant elements Cu and S is reported. Cu2‐xS surprisingly has lower thermal conductivity and more strikingly reduced specific heat compared to the heavier Cu2Se, leading to an increased zT to 1.7. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>